Membangun Generasi Unggul dengan “PINTAR MULYA” pada TK dan SD di Sukamulya Kecamatan Cikupa - Kimsen; Kismanah, Imas; Azis, Abdul (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Early childhood and primary education serve as a crucial foundation in shaping the character and competencies of the nation's future generations. The 'Pintar Mulya' program is a community-based initiative aimed at improving the quality of education for children in Sukamulya, Cikupa District, by strengthening institutions at the kindergarten (TK) and elementary school (SD) levels. This article seeks to describe the approach, implementation, and impact of the Pintar Mulya program on the quality of basic education and student development in the Cikupa District.